Implementasi Total Quality Management (TQM) dalam Proses Produksi di PT Mitra Alam Segar Pasuruan - Rahmi Pamel; Moch Gilang Luqman Hakim; Khairulis Shobirin (MABIS Jurnal Manajemen Bisnis Syariah, 2025)
This study aims to assess the effectiveness of Total Quality Management (TQM) in the manufacturing process at PT Mitra Alam Segar Pasuruan and to identify the supporting and inhibiting factors, as well as their impact on production efficiency and quality. The research method employed is qualitative research with a descriptive case study approach. The informants in this study consisted of 30 individuals, including management, production supervisors, and operational employees. Data collection techniques involved observation, interviews, and documentation. The interview instruments were designed according to TQM principles, namely continuous improvement, customer satisfaction, and employee participation. The collected information was processed through the stages of data reduction, data presentation, and conclusion drawing. The research findings indicate that the implementation of TQM at PT Mitra Alam Segar Pasuruan has been partially effective due to management's commitment to the concept, a culture of open communication, and continuous training. However, there are still obstacles such as employee resistance and a lack of inter-departmental coordination. Overall, the results of this study imply that TQM has been proven to enhance production process efficiency, reduce the frequency of product defects, and improve customer satisfaction